PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KEPEMILIKAN INSTITUSIONAL - Fenny Marietza; Dekker Yusuf Alfredo (UNIB Press, 2017)
disclosure on institutional ownership in the company. The company's institutional ownership is seen from the institutional ownership of shares in each company. The sample in this study is a company listed on the Stock Exchange Indonesia (IDX) in 2014-2015. Pursuant to sample purposive sampling method in this research is 94 company with observation 188 company. The results of this study indicate that CSR disclosure of community category has positive and insignificant effect on institutional ownership. On the other hand, CSR category disclosure of the Employment category and product category CSR have a negative and significant effect. Only CSR disclosure of environmental categories has a positive and significant influence on institutional ownership.Keywords : Disclosure of Corporate Social Responsibility (CSR), institutional ownership.